Making Quality Care Affordable for the Poor : Faith-Inspired Health Facilities in Burkina Faso - Gemignani, Regina; Tsimpo, Clarence; Wodon, Quentin (Taylor and Francis, 2014)
Faith-inspired institutions (FIIs) play an important role in improving health care in many African countries through the delivery of facility-based care, training of the health workforce, involvement in community-based activities, and participation in health promotion campaigns. FIIs represent a wide array of faiths and diverse motivations and goals. While a number of factors shape the approaches taken by FIIs in planning their activities, an often expressed priority is to serve the poor for whom care often remains unaffordable. Many faith-based providers also aim to provide preventive and/or curative care to those who are at a disadvantage or marginalized. In the case of Burkina Faso, significant progress has been achieved to facilitate access to care—examples include, among others, the construction of new facilities, vaccination campaigns, and the reduction or elimination of selected fees. As a result, many health statistics such as the rate of assisted childbirth, the use of health services, vaccination, and infant mortality have improved. Nevertheless, available household survey data suggest that apart from cases when an individual does not seek care because there is no need for it, or self-medicates when ill or sick, the main reason for not seeking care is cost.